Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1371/journal.pone.0157996
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Common Variants in Iron-Related Genes with Haematological Traits in Populations of African Ancestry

Abstract: BackgroundLarge genome-wide association (GWA) studies of European ancestry individuals have identified multiple genetic variants influencing iron status. Studies on the generalizability of these associations to African ancestry populations have been limited. These studies are important given interethnic differences in iron status and the disproportionate burden of iron deficiency among African ancestry populations.MethodsWe tested the associations of 20 previously identified iron status-associated single nucle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 58 publications
0
13
0
Order By: Relevance
“…Since there is evidence of genetic differences among population subgroups with regard to iron metabolism [ 66 ], we also compared levels of CSF iron, transferrin, and H-ferritin between self-reported HIV+ White, Black, and Hispanic study participants and were able to discern ancestry-related differences. As shown in Table 4 and Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Since there is evidence of genetic differences among population subgroups with regard to iron metabolism [ 66 ], we also compared levels of CSF iron, transferrin, and H-ferritin between self-reported HIV+ White, Black, and Hispanic study participants and were able to discern ancestry-related differences. As shown in Table 4 and Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The majority of the studies (59/64) were conducted in Europe, Asia and the USA (Fig 1, S2 Table). Only five studies were conducted in Africa, two in Rwanda [49,50], one in Zimbabwe [51], one in South Africa [52] and one meta-analysis across Kenya, Tanzania and South Africa [30]. Across the 64 studies, 50 SNPs were identified in six genes (TMPRSS6, HAMP, TF, TFR2, SLC40A1 and HFE) (S1 Table).…”
Section: Genetic Variants Associated With Iron Imbalancesmentioning
confidence: 99%
“…iron status measures and severity of haemochromatosis [50,51,[55][56][57]. One SNP was identified in HAMP (rs10421768) [30,55,[58][59][60] and one in TFR2 (rs7385804) (6,7,33,34,37,38), both of which were found to be associated with increases in haemoglobin and alterations serum in ferritin concentrations [30,55,56,58,[61][62][63]. For the HFE gene, we found four SNPs that have been associated with alterations in haemoglobin and/or an increase in the genetic risk of hereditary haemochromatosis [13,14,19,20,24,26,29,56,62,[64][65][66][67][68][69][70][71][72][73][74].…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…We will employ a recall-by-genotype study design, in which participant selection will be based on TMPRSS6 SNPs reported to be associated with the risk of iron-deficiency anaemia: rs855791, rs4820268 and rs2235321 10,14,15 . We will utilize the West African BioResouce (WABR), which contains the Kiang West Longitudinal Population Study (KWLPS) as the basis for selection of pre-genotyped participants 16 .…”
Section: Methodsmentioning
confidence: 99%